Pakistan : Fourth Review Under the Stand-By Arrangement, Requests for Waivers of Performance Criteria, Modification of Performance Criteria, and Rephasing of Access; Staff Report; Staff Statement and Supplement; Press Release on the Executive Board Discussion; and Statement by the Executive Director for Pakistan. (IMF Staff Country Reports; Country Report ;, 2010)
The 2010 staff report for the Fourth Review Under the Stand-By Arrangement addresses economic challenges faced by Pakistan. The implementation of the structural agenda faced delays but politically difficult reforms were assured to be executed. The resulting fiscal pressures had been expected to be largely offset by restraining nonpriority current spending. The authorities have shown their determination to pursue difficult, but necessary, reforms to implement the program despite lower-than-promised external assistance. IMF staff supported the requested rephasing of access and modifications to the performance criteria.